Conversation Implicature of Ustaz Abdul Somad in Processing Discourse - Nashihah Khumda; Rustono Rustono; Fathur Rokhman; Teguh Supriyanto (Universitas Negeri Semarang, 2022)
This study aims to describe conversational implicatures in Ustaz Abdul Somad's utterances in his preaching discourse. This research is a qualitative research that analyzes UAS utterances in the use of da'wah discourse. The data of this study are about the conversational implicatures of Ustadz Abdul Somad's da'wah discourse. The data was taken through a selection stage based on the needs that became the focus of the research, namely data in the form of conversational implicatures on Ustadz Abdul Somad's da'wah discourse. Data analysis and interpretation techniques were carried out with the stages of data collection, data reduction, data presentation, and drawing conclusions. The results and conclusions of this study are that there are conversational implicatures in Ustaz Abdul Somad's utterances in his da'wah discourse including implicatures of being patient, not careful, telling, ordering, asking permission, be careful, give alms, praising, ridiculing, and joking implicatures.